(untitled) (International Journal of Management and Sustainability, 2023)
This paper examines how mining, oil, and gas companies address environmental issues and communicate their actions to stakeholders through sustainability reports. Using market capitalization as a size metric, 50 mining, oil, and gas companies listed on the Indonesia Stock Exchange (IDX) were included in the research sample. Sustainability reports were subjected to quantitative and qualitative content analysis to identify keyword occurrences that were pertinent to the investigation. The findings revealed that environmental protection, emissions, carbon footprint, climate change, biodiversity, nature, planet, effluent, and conservation were addressed in the companies’ sustainability reports. This study confirmed, in line with research on other industries, that the intensity of communication on these topics varies with company size. It was also found that, although some companies discuss many keywords that correspond to the Global Reporting Initiative, they are irrelevant because the reports do not show the companies’ commitment and efforts to achieve the concepts. The practical implication of this research is that companies should show more commitment in their efforts to address environmental issues – sustainability disclosure is not just about words.